PENGARUH KONSENTRASI EKSTRAK KULIT BATANG JAMBU METE (Anacardium occidentale Linn) DALAM BAHAN KUMUR TERHADAP KEPADATAN KOLAGEN PADA PENYEMBUHAN LUKA (Kajian pada Guinea pig) - , WINADI SURYANATA WOE; , drg. Harsini, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mouthwash is a kind of solution that use for rinsing oral cavity with some purposes, such as therapeutic agents. Mouthwashes which contain herbal composition showed some advantages. Cashew stem bark contains alkaloids, flavonoids, tannins, saponins, anakardat acid, and cardol. The aim of this study was to determine the effect of concentration of cashew stem bark extract in a mouthwash to collagenâs density in the wound healing process (Studies on Guinea pig). Thirty-six of Guinea pigâs lower right incisive was extracted and divided into 3 kinds of treatment groups, the groups which was given cashew stem bark extract concentration of 3%, 5%, 7% in the morning and afternoon. Four Guinea pig from each group were then decapitated on day 3, 7, and 14, then their gingival and periodontal tissue were taken for histological specimens made with Trichrom Mallory. Density of collagen fibers was assessed from a score that range 0-4. The data obtained were then tested with Kruskal-Walis and Mann-Whitney tests. The results were showed that the mean of collagenâs density was increasing from day 3 to 14. Kruskal-Walis test was showed the effect of day and concentration (p < 0.05) to collagenâs density. Mann-Whitney test was showed a significant differences (p < 0.05) among the concentration of 3%, 5%, and 7% on each treatment day with the highest score collagenâs density was occured on the concentration of 7%. The conclusion of this study was the concentration of cashew stem bark extract and days affects the density of collagen.